2021
DOI: 10.1186/s13293-020-00355-y
|View full text |Cite
|
Sign up to set email alerts
|

Important differences between hypertensive middle-aged women and men in cardiovascular autonomic control—a critical appraisal

Abstract: Background Normotensive premenopausal women show a vagal predominance of cardiac autonomic modulation, whereas age-matched men show a predominance of sympathetic modulation. However, some women develop systemic arterial hypertension (SAH) even with preserved ovarian function. Our hypothesis is that these women may have cardiovascular autonomic parameters similar to those of hypertensive men, even when subjected to pharmacological treatment. We aimed to investigate cardiovascular autonomic contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
12
0
5
Order By: Relevance
“…In this case, HRV indices are important markers of an increased risk of cardiac events and sudden death in these individuals. 7,21,[26][27][28]…”
Section: Heart Rate Variability and Diseases Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, HRV indices are important markers of an increased risk of cardiac events and sudden death in these individuals. 7,21,[26][27][28]…”
Section: Heart Rate Variability and Diseases Cardiovascular Diseasesmentioning
confidence: 99%
“…127,137 More recent studies have shown that women before menopause have lower oscillations of the sympathetic autonomic component and greater oscillations of the cardiac vagal autonomic component when compared to age-matched men (Figure 2), 69,70,138,139 including individuals with a history of systemic arterial hypertension. 26 The causes of these differences have not been fully elucidated; however, the beneficial effect of ovarian hormones on cardiovascular autonomic control is a very important variable, since estrogens seem to be able to increase the vagal influence on the heart, in addition to reducing the sympathetic influence on the heart and vascular beds. [140][141][142] These effects are consistent with other studies that observed autonomic impairments resulting from ovarian failure, such as a reduction in HRV and baroreflex sensitivity.…”
Section: Cautions With Using Hrv Analysismentioning
confidence: 99%
“…The choice to include only men was based on previous studies, which showed that men and women have differences in cardiac autonomic modulation balance. In this case, the men had a greater predominance of the sympathetic autonomic component [22][23][24].…”
Section: Samplingmentioning
confidence: 77%
“…Among these impairments, adverse cardiac morphological and functional adaptations and cardiovascular autonomic control changes are the most common and often associated with a less favorable prognosis ( 3 - 6 ). However, little is known about the contribution of ovarian hormones to autonomic and morphofunctional cardiac protection due to SAH.…”
Section: Introductionmentioning
confidence: 99%